Corporate social responsibility and its communication on Twitter: analysis of the discourse and feelings generated in society - Cuervo Carabel, Tatiana; Arce García, Sergio; Orviz Martínez, Natalia (Cuadernos de Gestión, 2023)
The purpose of this work is to analyze on a global level, without focusing on any specific company or sector, the use that is being made of the social media Twitter to address the communication processes of CSR in companies. To do this, data was captured through programming in R and using an Application Program Interface (API) in Twitter. The data were analyzed using text mining techniques and graphical network analysis with the help of R and Gephi software, respectively. The results show that there are no notable groups or movements in the corporate sphere as generators of CSR content. The importance of the social perspective of CSR in communication processes should be emphasized. Finally, CSR generates positive feelings and emotions such as trust in society. It is concluded that there is no efficient use by companies of Twitter as a CSR communication tool, they are not taking into account the interests of their stakeholders, nor are they generating the dialogue and interaction necessary for communication to be effective. The main limitation is associated with the time period in which the sample was taken, which coincides with a period of strong social concern about the pandemic. It would be interesting for future research to analyze how the discourse changes over time, and to what extent an extraordinary social situation, such as the pandemic, is reflected in CSR communication.
Keywords: CSR; Twitter; communication; corporate; social; responsibility; Emerging